Topography of the Human Papillomavirus Minor Capsid Protein L2 during Vesicular Trafficking of Infectious Entry - DiGiuseppe, Stephen (J Virol, 2015)
The human papillomavirus (HPV) capsid is composed of the major capsid protein L1 and the minor capsid protein L2. During entry, the HPV capsid undergoes numerous conformational changes that result in endosomal uptake and subsequent trafficking of the L2 protein in complex with the viral DNA to the trans-Golgi network. To facilitate this transport, the L2 protein harbors a number of putative motifs that, if capable of direct interaction, would interact with cytosolic host cell factors. These data imply that a portion of L2 becomes cytosolic during infection. Using a low concentration of digitonin to selectively permeabilize the plasma membrane of infected cells, we mapped the topography of the L2 protein during infection. We observed that epitopes within amino acid residues 64 to 81 and 163 to 170 and a C-terminal tag of HPV16 L2 are exposed on the cytosolic side of intracellular membranes, whereas an epitope within residues 20 to 38, which are upstream of a putative transmembrane region, is luminal. Corroborating these findings, we also found that L2 protein is sensitive to trypsin digestion during infection. These data demonstrate that the majority of the L2 protein becomes accessible on the cytosolic side of intracellular membranes in order to interact with cytosolic factors to facilitate vesicular trafficking. IMPORTANCE In order to complete infectious entry, nonenveloped viruses have to pass cellular membranes. This is often achieved through the viral capsid protein associating with or integrating into intracellular membrane. Here, we determine the topography of HPV L2 protein in the endocytic vesicular compartment, suggesting that L2 becomes a transmembrane protein with a short luminal portion and with the majority facing the cytosolic side for interaction with host cell transport factors.